The Lottie project - Wilson, Jacqueline (London : Corgi Yearling, 2007)
Jacqueline Wilson's story in which Charlie finds her "easy-peasy, simple-pimple" school year changing when her strict teacher assigns a tough school project and her mother loses her job.
Young Adult
Keywords: Mothers and daughters -- Juvenile literature; Schools -- Juvenile literature; Single-parent families -- Juvenile literature; Mothers and daughters -- Fiction; Schools -- Fiction; Single-parent families -- Fiction; Mother-daughter relationship -- Fiction; Schools -- Fiction; Single-parent families -- Fiction